Assessments of Semilocal Density Functionals and Corrections for Carbon Dioxide Adsorption on Metal–Organic Frameworks. Issue 15 (28th August 2014) - Ji, Hyunjun; Park, Joonho; Cho, Moses; Jung, Yousung
Abstract The significant amount of attention that has been directed toward metal–organic frameworks (MOFs) for a wide spectrum of applications can be attributed to their variety and tunability, which are precisely the aspects that computational modeling can offer by systematically exploring the chemical space. In this minireview, we describe density functional theory calculations for gas adsorption on MOFs, mainly focusing on the interaction of CO2 with MOF‐74. The generalized gradient approximation (GGA) level of density functional studies seems suited to treat MOFs, owing to the balance between its practical applicability and its useful accuracy, although this method is not without deficiencies such as the lack of nonlocal correlations and self‐interactions. We review and analyze the effects of correction schemes to the GGA to amend the latter weaknesses, and the choice of exchange correlation functionals to treat MOFs for gas capture and separation. We also discuss a few topical questions that are currently missing in the present literature and that require further investigations.